Pengaruh Keterikatan Kerja, Dukungan Sosial, Dan Kapabilitas Terhadap Kepuasan Kerja Guru Di MAN 2 Mojokerto - Budiarti, Riza Agustin; Dewianawati, Dwi; Budiyanto, Fajar (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
From the results of observations or observations, several problems were found that occurred in teacher job satisfaction. Problems that cause a lack of work engagement, social support and capability for teachers. The aim of this research is to find out how work engagement, social support and work engagement influence teacher job satisfaction at MAN 2 Mojokerto. Quantitative techniques were used in this research. The population in this research is non-permanent teachers or GTT at MAN 2 Mojokerto. 35 GTT (non-permanent teachers) at MAN 2 Mojokerto answered the questionnaire used to collect research data. The method used is by distributing questionnaires via the Googleform application. The sampling technique used is the total sampling technique. The data analysis method used is multiple regression analysis, hypothesis testing. The research results show that: teacher performance satisfaction at MAN 2 Mojokerto is significantly influenced by the work engagement component with a t value of -2.342 and a significance of 0.026 > 0.05. According to the research results, teacher job satisfaction at MAN 2 Mojokerto is not influenced by social support with a value of t 0.173 and significance 0.863 <0.05. Based on the research results, it is known that capability has a significant effect on teacher job satisfaction at MAN 2 Mojokerto with a t value of 2.891 and a significance of 0.0007 < 0.05